2020
DOI: 10.3390/jcm9051369
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Gut Microbiome Fermentative Pathways in Fatty Liver Disease Progression

Abstract: Non-alcoholic fatty liver disease (NAFLD) is a multifactorial disease in which environmental and genetic factors are involved. Although the molecular mechanisms involved in NAFLD onset and progression are not completely understood, the gut microbiome (GM) is thought to play a key role in the process, influencing multiple physiological functions. GM alterations in diversity and composition directly impact disease states with an inflammatory course, such as non-alcoholic steatohepatitis (NASH). However, how the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 130 publications
(159 reference statements)
0
21
0
3
Order By: Relevance
“…NASH is a more severe form of NAFLD, it encompasses a range of distinct pathological features in the liver, including hepatocellular ballooning, hepatocyte injury, liver inflammation, steatosis and fibrosis and can further progress to liver cirrhosis and HCC 37‐39 . Our previous study revealed that VVYP could reduce serum AST and ALT, improve the pathological state of liver tissue, and protect against liver injury caused by carbon tetrachloride or paracetamol in mice 33 .…”
Section: Discussionmentioning
confidence: 99%
“…NASH is a more severe form of NAFLD, it encompasses a range of distinct pathological features in the liver, including hepatocellular ballooning, hepatocyte injury, liver inflammation, steatosis and fibrosis and can further progress to liver cirrhosis and HCC 37‐39 . Our previous study revealed that VVYP could reduce serum AST and ALT, improve the pathological state of liver tissue, and protect against liver injury caused by carbon tetrachloride or paracetamol in mice 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The GM can also inhibit hepatic lipid synthesis by regulating BAs metabolism to alter FXR signaling pathways ( Iruzubieta et al, 2020 ). Studies have found that glycine may be directly related to the occurrence of NAFLD.…”
Section: Gm and Metabolic Diseasesmentioning
confidence: 99%
“…Who is responsible for this altered IP remains an open question in NAFLD physiopathology. An altered "dysmetabolic" gut microbiota could be the answer [76][77][78]. This obesogenic intestinal microbiota has been linked to the development of insulin resistance through the LPS/TLR4/CD14 systems [79].…”
Section: Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%